ТНЕ DEVELOPMENT OF SCIENCE FICTION AS A LITERARY GENRE (Ta'limning zamonaviy transformatsiyasi, 2025)
ABSTRACT: This article examines science fiction is a vibrant and lasting literary genre that delves into futuristic settings, advanced technologies, space travel, time manipulation, and the impacts of scientific progress. It provides a framework for readers to investigate societal constructs, human behavior, and the potential future, blending imaginative storytelling with elements of scientific plausibility. While its origins can be traced back centuries, science fiction firmly established itself as a distinct force in modern literature during the 19th and 20th centuries.